The influence of the environment and work culture on organizational performance through strategic planning at the community and village empowerment services in Flores district, East Nusa Tenggara province - Mersiana Varia Juita (Indonesia Auditing Research Journal, 2022)
This study aims to determine the effect of environmental strategy, organizational culture, and planning strategy on organizational performance at the Village Community Empowerment Agency of the Provincial Government of Flores Regency, East Nusa Tenggara. The sample of this study was 100 residents of Flores Regency. Partial Least Square (PLS) was used as a hypothesis testing tool. The results showed that organizational culture has an effect on organizational situation, and strategic planning has an effect on organizational performance, according to the findings of this study. In addition, the strategic environment has an effect on strategic planning, and organizational culture has an effect on strategic planning.